2018
DOI: 10.17221/146/2017-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of distance methods for estimating population density in Populus euphratica Olivier natural stands (case study: Maroon riparian forests, Iran)

Abstract: Basiri R., Moradi M., Kiani B., Maasumi Babaarabi M. (2018): Evaluation of distance methods for estimating population density in Populus euphratica Olivier natural stands (case study: Maroon riparian forests, Iran). J. For. Sci., 64: 230-244.The aim of this study was to determine the performance of distance methods in terms of accuracy, precision, bias, consumed time and sampling efficiency in the Maroon riparian forests, Iran. 40 estimators were used to evaluate the density of Populus euphratica Olivier trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Therefore, the effectiveness of a plotless density estimator must be evaluated considering its performance in non-random patterns and especially in clustered patterns, which are more frequent in real forests (Engeman et al 1994). Many studies confirmed the robustness of PCQM towards the bias related to non-random patterns (Engeman et al 1994, White et al 2008, Khan et al 2016, Basiri et al 2018, Jamali et al 2020. Additionally, in our findings the PCQM provided estimates comparable to PSM.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, the effectiveness of a plotless density estimator must be evaluated considering its performance in non-random patterns and especially in clustered patterns, which are more frequent in real forests (Engeman et al 1994). Many studies confirmed the robustness of PCQM towards the bias related to non-random patterns (Engeman et al 1994, White et al 2008, Khan et al 2016, Basiri et al 2018, Jamali et al 2020. Additionally, in our findings the PCQM provided estimates comparable to PSM.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 62%
“…Furthermore, in our results, the plot-based estimates do not differ from those of PCQM, in terms of both accuracy and precision. Despite the higher field efforts required, due to the identification of the four equal-angular sectors, the PCQM proved to be the most effective method for a variety of forests (Ahmed & Ogden 1987, Kumarathunge et al 2011, Khan et al 2016, Basiri et al 2018, Jamali et al 2020.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%